High accuracy characterisation system for conductometric metal oxide gas sensors. (1st January 2014) - Addabbo, Tommaso; Bertocci, Francesco; Fort, Ada; Mugnaini, Marco; Vignoli, Valerio; Shahin, Luay; Rocchi, Santina
A measurement system designed for the characterisation of chemorestive sensors based on novel materials is described. The system allows to simultaneously test up to eight sensors. It exploits an ad hoc structure based on an alumina substrate equipped with electrodes, a heater and an accurate temperature sensor, on which the material under study can be easily deposited by screen printing, spin coating or dip coating. The system is designed to study the behaviour of the sensors by accurately setting the working conditions in terms of chemical environment composition, gas flow, humidity and temperature. In particular the temperature of each sensor under test can be individually set by a digital control loop to a constant value or can be forced to follow an arbitrary time profile. The control system measures the sensing film temperature with a resolution close to 0.1°C and sets it with an uncertainty close to 1°C. Both chemical transients and thermal transients can be studied. These features make this system suitable for determining the principal performance indexes of a gas sensing device (e.g., sensitivity, stability, selectivity, response/recovery times, etc.) as functions of various combinations of measurement conditions (e.g., gas concentrations, temperature, humidity, flow).